Football Game Development Moving Wicket - Ardin Abdul Gani; Arief Ibnu Haryanto; Gilang Ramadan; Giofandi Samin; Iwan Fataha; Sulasikin Sahdi Kadir (Halaman Olahraga Nusantara : Jurnal Ilmu Keolahragaan, 2021)
The sport of football is a game that is very popular in all circles; it is proven that in every region that has a football field, there must be someone who plays either from achievement or to fill in his spare time. Therefore, this research aims to develop a football game that moves. This research method is development research that has been modified, starting from preliminary studies to testing products that have been designed. The result of this research is that a mobile goal football development product was created as a learning medium for junior high schools, which is adjusted to the level of development and growth of students.